Legal Protection for Customers Regarding Interest on Digital Bank Deposits Exceeding the Limits Set by the Deposit Insurance Agency - Irfandi, Muhamad Fajar; Setiawan, Andry (Semarang State University Undergraduate Law and Society Review, 2025)
The presence of digital banks in Indonesia has also raised issues related to high-interest deposits that exceed the limits stipulated by the Deposit Insurance Corporation (LPS). This risks harming customers if the bank defaults, goes bankrupt, or goes into liquidation. Therefore, it is important to examine the legal provisions of digital banks and legal protection for customers for these deposits. This research is normative with a qualitative approach, using secondary data analyzed through literature studies. The results of the study show that the provisions regarding digital banks have been regulated in POJK Number 12/POJK.03/2018 and POJK Number 12/POJK.03/2021, but are still limited to the POJK level which has lower legal force, so strengthening is needed through special laws. Legal protection for customers is regulated preventively through Law Number 8 of 1999 and POJK Number 6/POJK.07/2022, as well as repressively through complaint and compensation mechanisms. However, this protection is not yet optimal because there are no specific regulations requiring digital banks to provide clear information regarding deposits that are not guaranteed by LPS and the absence of effective sanctions for transparency violations.